A phytochemical investigation of the volatile oil of Wedelia biflora (Linn.) DC. (Family Compositae) - Chavez, Dario Gabriel M.; Castillo, Amorita V.; Concepcion. Adoracion B. (Quezon City: College of Pharmacy, University of the Philippines, 1979.)
Wedelia biflora is a climbing, somewhat rough, herbaceous vine. The leaves are opposite ovate, and 6 to 8 cm long, with pointed top and rounded base, rather coarsely toothed margin, and stalks 2 to 6 cm long. The heads are 3 cm in diameter or less, and number 1 to 3, sometimes more in the upper axils, with stalks 7 to 10 cm long.
Wedelia biflora is locally known as Hagonoi and is abundant in thickets back of beaches and along tidal streams throughout the Philippines. It is also grown along main and side streets of Metro Manila as an ornamental plant.
This specis is to be distinguished from other type of Wedelia, the Wedelia chinensis or locally known as Hagonoi-tsina which is slender, spreading, and hairy. The leaves being oblong to oblong-lanceolate, 2 to 4.5 cm in length and narrowed at both ends, the margin entire or obscurely toothed. Both surfaces are covered with sharp-pointed, appressed, straight, and stiff hairs.
The plant was found to contain about 83.4% moisture thus leaving about 16.6% as active constituent. The percentage yield of the volatile oil is from 0.71% to 0.76%.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines, 1979.
Keywords: Compositae; Hagonoi; Hagonoi-tsina.